2000
DOI: 10.1007/s100240010104
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Malformation of Ductal Plate of the Liver in Meckel Syndrome and Review of Other Syndromes Presenting with this Anomaly

Abstract: Meckel syndrome (MIM 249.000) is an autosomal recessive disorder with a variable spectrum of anomalies. Since the first reports of this syndrome, very broad diagnostic criteria have been proposed, but the process of defining them continues. It is probable that at least two of three manifestations, including cystic kidney dysplasia, occipital encephalocele or other anomaly of the central nervous system, and postaxial polydactyly occur in most cases. Arrest of the development of intrahepatic bile ducts at the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 33 publications
1
51
0
1
Order By: Relevance
“…All these three anomalies (triad) were found in our case. According to Sergi et al [8], polycystic kidneys were found in all cases (100%), occipital encephalocele in 90% of case and post-axial polydactyly in 83.3% of cases. Salonen et al [5] found a constant association between cystic dysplasia and liver fibrosis, and concluded that these two abnormalities, together with any other abnormalities of the nervous system, suffice to diagnose MGS.…”
Section: Discussionmentioning
confidence: 91%
“…All these three anomalies (triad) were found in our case. According to Sergi et al [8], polycystic kidneys were found in all cases (100%), occipital encephalocele in 90% of case and post-axial polydactyly in 83.3% of cases. Salonen et al [5] found a constant association between cystic dysplasia and liver fibrosis, and concluded that these two abnormalities, together with any other abnormalities of the nervous system, suffice to diagnose MGS.…”
Section: Discussionmentioning
confidence: 91%
“…These features are found in 100%, 90%, and 83.3% of the fetuses, respectively. [9]. Microcephaly, encephalocele and rhombic roof dysgenesis should also be included in the diagnostic criteria of MGS [10].…”
Section: Casementioning
confidence: 99%
“…Subsequently, one or two immature, mostly peripherally located ductular structures transform into mature interlobular bile ducts, while most of them gradually disappear (Sergi et al, 2008a). The transformation of the ductal plate into mature interlobular bile ducts is accompanied by the expression of specific intermediate filaments of the cytoskeleton, the cytokeratins (CK) (Van Eyken et al, 1988;Sergi et al, 2008b;Sergi et al, 2000a). Epithelial cells forming bile ducts express CK-7 and CK-19 in addition to CK-8 and CK-18, the latter two being also positive in normal adult hepatocytes.…”
Section: Development Of Intrahepatic Biliary Systemmentioning
confidence: 99%
“…The complete or partial persistence of the primitive doublelayered cylinder of biliary-type cells in the developing liver gives rise to portal tracts with an increased number of bile duct structures. The term "ductal plate malformation of the liver" was coined to label this complex biliary plexus with an excess of primitive bile duct structures (Sergi et al 2000a;Sergi et al 2000b;Sergi et al 2000c). Previously, we examined the patterns of cytokeratin 7 (CK7) expressing biliary structures of liver biopsies of infants aged less than one year and found specific patterns in biliary atresia, neonatal hepatitis (a category of inflammation of the liver probably including several conditions showing lobular disarray of the hepatocytes and giant cell transformation as well as presence of extramedullary hematopoiesis) and paucity of the intrahepatic bile duct system or paucity of the interlobular bile ducts (PIBD).…”
Section: Ductal Plate Malformationmentioning
confidence: 99%